Temporal Dynamics of Chronic Inflammation on the Cecal Microbiota in IL-10-/- Mice - Overstreet, Anne-Marie C.; Ramer-Tait, Amanda E.; Suchodolski, Jan S.; Hostetter, Jesse M.; Wang, Chong; Jergens, Albert E.; Phillips, Gregory J.; Wannemuehler, Michael J. (Frontiers in Immunology, 2021)
The intestinal microbiota is a critical component of mucosal health as evidenced by the fact that alterations in the taxonomic composition of the gastrointestinal microbiota are associated with inflammatory bowel diseases. To better understand how the progression of inflammation impacts the composition of the gastrointestinal microbiota, we used culture independent taxonomic profiling to identify temporal changes in the cecal microbiota of C3Bir IL-10-/- mice concomitantly with the onset and progression of colitis. This analysis revealed that IL-10-/- mice displayed a biphasic progression in disease severity, as evidenced by histopathological scores and cytokine production. Beginning at four weeks of age, pro-inflammatory cytokines including TNF-alpha, IFN-gamma, IL-6, G-CSF, and IL-1 as well as chemokines including RANTES and MIP-1 were elevated in the serum of IL-10-/- mice. By 19 weeks of age, the mice developed clinical signs of disease as evidenced by weight loss, which was accompanied by a significant increase in serum levels of KC and IL-17. While the overall diversity of the microbiota of both wild type and IL-10-/- were similar in young mice, the latter failed to increase in complexity as the mice matured and experienced changes in abundance of specific bacterial taxa that are associated with inflammatory bowel disease in humans. Collectively, these results reveal that there is a critical time in young mice between four to six weeks of age when inflammation and the associated immune responses adversely affect maturation of the microbiota.